Observation of Interfacial Damage in a Silk‐Epoxy Composite, Using a Simple Mechanoresponsive Fluorescent Probe. Issue 10 (17th March 2017) - Woodcock, Jeremiah W.; Beams, Ryan; Davis, Chelsea S.; Chen, Ning; Stranick, Stephan J.; Shah, Darshil U.; Vollrath, Fritz; Gilman, Jeffrey W.
Abstract : Polymer composites are found throughout the world both natural and artificial in origin. In the vast majority of applications, composites serve as structural support or reinforcement roles. Demand for lightweight tough composites is growing in multiple application spaces such as areospace, biomaterials, and infrastructure with physical properties as diverse as the applications. The unifying component in all composites is the presence of an interphase. Many measurement techniques and measurement tools have been developed for the study of this crucial region in composite materials. Many of these methods are great for the measurment and study of bulk properties or model systems. However, development of methods that permit the direct observation of interactions at the interphase during applied stress are needed. Here we employ fluorescence lifetime imaging and hyperspectral imaging to observe activation of a fluorogenic dye at the composite interface as a result of applied stress. The advantages of this sytem include commercial availability of the dye precursor, and simple one‐pot functionalization. The attachment of the dye at the interface is easily monitored through emission wavelength shifts and fluorescence lifetime variations. Interfacial mechano‐responsive dyes have potential for both fundamental studies as well as industrial use as a structural health monitoring tool. Abstract : Hundreds of micrometers inside a silk fiber composite, two‐photon fluorescence life‐time imaging, and hyperspectral imaging of a damage‐sensing probe (mechanophore), reveals interface debonding, fiber fracture, and chemical reaction with the matrix. Functional groups on the periphery of the fluorescent probe chemically link the fiber and matrix. Stress transfer across the probe's strained spirolactam center activates the probe's fluorescent properties.